THE EFFECT OF PRUDENCE, FINANCIAL DISTRESS, AND INSTITUTIONAL OWNERSHIP ON TAX AVOIDANCE WITH LEVERAGE AS A MODERATION VARIABLE - Ranggala, Qadar; Duni, Duni; Rambe, Hikma Agustina; Kurniaaningsih, Ika (Univesitas Muhammadiyah Tangerang, 2025)
The purpose of this study was to determine the effect of prudence, financial distress and institutional ownership on tax avoidance with leverage as a moderating variable in primary consumer goods manufacturing companies (Consumer Non-Cyclicals) listed on the Indonesia Stock Exchange (IDX). The research time period is 5 years, namely the 2018-2022 period. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. The sampling technique uses purposive sampling technique. Based on the predetermined criteria, 16 companies were obtained. The type of data used is secondary data obtained from the Indonesian Stock Exchange website. The analytical method used is Moderated Regression Analysis (MRA) with the help of SPSS version 25 software. The results of this study partially show that Prudence, financial distress, and Institutional Ownership have a significant effect on tax avoidance. Leverage is unable to moderate the relationship between prudence, financial distress and institutional ownership on tax avoidance.